Biological testing of ships’ ballast water indicates challenges for the implementation of the Ballast Water Management Convention - Outinen, Okko; Bailey, Sarah A.; Casas-Monroy, Oscar; Delacroix, Stephanie; Gorgula, Sonia; Griniene, Evelina; Kakkonen, Jenni E.; Srebaliene, Greta (Frontiers in Marine Science, 2024)
Ships' ballast water and sediments are vectors that contribute to the unintentional spread of aquatic non-native species globally. Ballast water management, as well as commissioning testing of ballast water management systems and compliance monitoring under the regulations of the International Maritime Organization (IMO) aim at minimizing the unwanted spread of organisms. This study compiles data for treated ballast water samples collected and analyzed from 228 ships during 2017-2023. The samples were collected from the ballast discharge line or directly from the ballast tank for enumeration of living organism concentrations in the categories of ≥50µm and <50 to ≥10µm -sized organisms, as well as indicator microbes in comparison to the ballast water performance standard of the IMO (Regulation D-2). In addition, several ship-specific factors were examined to infer potential factors affecting compliance rates. Nearly all ships were compliant with the ballast water performance standard for indicator microbes and <50 to ≥10µm -sized organisms, whereas almost half of all samples exceeded the limit of ten viable organisms m -3 for the ≥50µm -sized organisms. Compliance testing results did not differ significantly between sampling years, indicating that compliance rate did not change through time. The rate of compliance was higher for commissioning testing than compliance testing. Clear ship-or system-specific factors that lead to compliance or noncompliance were not detected, even though type of ballast water management system, filter mesh size associated with the system and source of ballast water affected compliance significantly either for the samples taken from the discharge line, or ballast tank. As compliance did not improve significantly over time, compliance testing of ships' ballast water should be undertaken to ensure that the systems remain operational after commissioning and ships meet requirements of the D-2 standard. Furthermore, the study outcomes promote further research on the efficiency of filter mesh sizes and different filtration units associated with ballast water management systems, to improve mechanical removal of larger organisms. Finally, as several ships exceeded the compliance limit by hundreds or thousands of living organisms, technological advancements and operational measures may be needed to improve the overall reliability of ballast water management.